Aravind Eye Care System : time to shift gears - Chandwani, Rajesh; Jha, Mithileshwar; Nagadevara, V. (London : Indian Institute of Management, Ahmedabad, 2015)
Dr. Aravind (Director, Projects, Aravind Eye Care System) could feel the September heat as he glanced through the activity summary report of Aravind Eye Care System (AECS) for 2013. Various thoughts crossed his mind. Though Aravind Eye Care System (AECS) had had a dream run on the growth path, it faced a major question, 'what next?'. The organisation prepared itself to catapult into a new orbit of growth, articulated in its vision 20-20, where AECS aimed at extending primary eye care to a population of one billion and reaching a target of one million surgeries and laser procedures. With the departure of the founder Dr. Venkataswamy Govindappa, and the founder generation giving way to the next generation, AECS was now in the hands of a new leadership. The new leadership was aware of the huge expectation associated with the responsibility of steering a large organisation with a successful past. Would the next generation leadership of AECS be able to take the organisation to the next orbit of growth?
Originally published in Chandwani, R., Jha, M., & Nagadevara, V. (;2015). Aravind Eye Care System: Time to shift gears.CMHS0037. Ahmedabad: Indian Institute of Management, Ahmedabad.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Aravind, S., -- Dr; Ophthalmology -- India; Medical care -- India; Health planning -- India; Eye -- Care and hygiene -- India